2021
DOI: 10.18103/mra.v9i8.2540
|View full text |Cite
|
Sign up to set email alerts
|

Body composition, fitness, and eating behaviors deteriorate during the COVID-19 pandemic in at-risk pediatric patients

Abstract: The COVID-19 pandemic has significantly altered children's daily routines. The health impacts of our obesogenic environment are exacerbated by COVID-19. Many clinicians have concerns that the lack of structured activity, increased stress and altered eating behaviors would lead to increases in adiposity in children. The present study examined changes in body composition as a result of the COVID-19 pandemic in pediatric patients in larger bodies and demonstrates significant increases in total body fat, percent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Comparisons of oxygen uptake and the anaerobic threshold between the pre and post-COVID-19 cohorts indicated that the post-COVID cohort oxygen uptake were significantly lower than in the pre-COVID cohorts (39.1 vs. 44.7, p =0.031) (38). The same was observed in Canadian elementary school-aged children (39). Authors suggest that increases in BMI, overweight, and obesity rates contribute to changes in pre-to post-pandemic health, such as in lower levels of physical fitness and HQoL (40).…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Comparisons of oxygen uptake and the anaerobic threshold between the pre and post-COVID-19 cohorts indicated that the post-COVID cohort oxygen uptake were significantly lower than in the pre-COVID cohorts (39.1 vs. 44.7, p =0.031) (38). The same was observed in Canadian elementary school-aged children (39). Authors suggest that increases in BMI, overweight, and obesity rates contribute to changes in pre-to post-pandemic health, such as in lower levels of physical fitness and HQoL (40).…”
Section: Discussionmentioning
confidence: 59%
“…These results are expected hypothetically, considering the complex interpretation including HQoL, fitness, and physical activity presented on the literature, even though, is important to point out that is a scarce kind of analytical longitudinal analysis in children during the years 2019-2022 (1)(2)(3)6,9,12,13,15,22,23,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations